Factors associated with low birth weight among the babies delivered at maternity hospital - Pahari, Sirjana Pandit; Mishra, Tulashi Adhikari (Journal of Kathmandu Medical College, 2015)
Background: Neonates with a birth weight of less than 2500 g have a higher risk of morbidity and mortality than the babies of normal birth weight. Various factors may play the role in the incidence of low birth weight babies.Objectives: The objective of the study was to fi nd out the factors associated with low birth weight in a maternity hospital.Methods: A case control study was conducted at Paropakar Maternity and Women’s Hospital Kathmandu. Non probability consecutive sampling method was applied in which the total study sample was 136. Among them 68 full term low birth weight babies as case and equal number of full term normal birth weight babies were included as control. Descriptive and inferential statistics were used for data analysis.Results: Half (50.0%) of the case mothers had history of previous low birth weight babies in comparision to 3.0% of the control mothers who had history of previous low birth weight babies. In regards to history of previous birth interval, 25.0% of cases and 3.0% of control mothers had history of previous birth interval of less than two years. Among those who had ANC visits, 40.0% of cases and 14.3% of controls had inadequate Antenatal visit during their last pregnancy. Study found a signifi cant association of low birth weight with smoking during pregnancy (p = 0.029) history of previouschild with term LBW (p= 0.001), birth spacing (p = 0.009) and antenatal visit during pregnancy (p =0.001) among the case mothers.Conclusions: The study concludes that the incidence of low birth weight babies tends to be higher among the mothers with history of smoking during pregnancy, with birth spacing of less than two years, and who had less than four antenatal visits.Journal of Kathmandu Medical CollegeVol. 3, No. 4, 2014Page: 153-157